Efficacy and safety of semaglutide on weight loss in obese or overweight patients without diabetes: A systematic review and meta-analysis of randomized controlled trials - Xueqin Gao; Xueqin Gao; Xiaoli Hua; Xiaoli Hua; Xu Wang; Xu Wang; Wanbin Xu; Wanbin Xu; Yu Zhang; Yu Zhang; Chen Shi; Chen Shi; et al. (Frontiers Media S.A., 2022)
Objectives: This study aims to explore the weight loss effect and safety of semaglutide as a conventional anti-obesity drug systematically in obese or overweight patients without diabetes.Methods: The randomized controlled trials (RCTs) of semaglutide in obese or overweight patients without diabetes were retrieved from PubMed, Cochrane Library, EMBASE, and ClinicalTrials.gov from database inception until 2 May 2022. Data extraction and quality assessment of studies meeting the inclusion criteria were performed, and statistical analysis was conducted by Review Manager 5.3 and Stata 14.Results: Eight studies involving 4,567 patients were enrolled in the meta-analysis. Compared with placebo, semaglutide induced a significant body weight loss (MD: −10.09%; 95% CI: −11.84 to −8.33; p ˂ 0.00001), elicited a larger reduction in body mass index (MD: −3.71 kg/m2; 95% CI: −4.33 to −3.09; p ˂ 0.00001) and waist circumference (MD: −8.28 cm; 95% CI: −9.51 to −7.04; p ˂ 0.00001), achieved weight loss of more than 5, 10, 15, and 20% with a higher proportion of participants. Semaglutide exhibited a positive effect on blood pressure, C-reactive protein, and lipid profiles, expressed more adverse effects than placebo, mainly gastrointestinal reactions. The results were stable and reliable with dose-dependence.Conclusion: Semaglutide indicated a significant weight loss with an acceptable safety for obese or overweight patients without diabetes.